Combined Effect of Levofloxacin and N-Acetylcysteine against Enterococcus faecalis Biofilm for Regenerative Endodontics: An in Vitro Study - Rastegar Khosravi, Mohammad; Khonsha, Masoumeh; Ramazanzadeh, Rashid (Iranian Endodontic Journal, 2019)
Introduction: Endodontic treatment of necrotic immature teeth poses several clinical challenges. A major problem is the elimination of microorganisms from the root canal system. This study evaluates the in vitro antibacterial efficacy of ciprofloxacin (CIP), levofloxacin (LEV), and their combination with N-acetylcysteine (NAC) in root canals infected with Enterococcus faecalis (E. faecalis). Methods and Materials: A total of 120 human extracted teeth with single canals were prepared and randomly divided into six groups: Calcium hydroxide (CH), ciprofloxacin (CIP), levofloxacin (LEV), ciprofloxacin and N-acetylcysteine (CIP+NAC), levofloxacin and N-acetylcysteine (LEV+NAC), and normal saline as a positive control. According to the name of the groups, intracanal medicaments were placed into the canals and the teeth were restored with a temporary filling. After one week, intracanal medicament was removed and the final count of bacteria was measured. Antibacterial effect of medicament was assessed by measuring the percentage reduction in the colony counts (RCC) and scanning electron microscopy (SEM). The Mann-Whitney U test and the Kruskal-Wallis test were used to compare the overall antibacterial efficacy of the intracanal medicaments at significance level of 0.05. Results: All intracanal medicaments were significantly more effective than calcium hydroxide (P<0.05). The combination of LEV and NAC caused significantly higher reduction in colony count in comparison with other tested medicaments (P=0.001). Conclusion: The combination of LEV and NAC showed greater antibacterial activity compared with other tested medicaments against biofilm of E. faecalis. Thus, it has the potential to be used in regenerative endodontic treatments. Keywords: Antibiotics; Biofilm; Enterococcus faecalis; Regenerative Endodontics